2015
DOI: 10.1161/strokeaha.115.010815
|View full text |Cite
|
Sign up to set email alerts
|

n -3 Polyunsaturated Fatty Acids Reduce Neonatal Hypoxic/Ischemic Brain Injury by Promoting Phosphatidylserine Formation and Akt Signaling

Abstract: Background and Purpose— Omega-3 polyunsaturated fatty acids ( n-3 PUFAs) attenuate neonatal hypoxic/ischemic (H/I) brain damage, but the underlying mechanisms are not fully understood. This study tested the hypothesis that n-3 PUFAs enhance Akt-dependent prosurvival signaling by promoting the biosynthesis of phosphatidylserine in neuronal cell membranes. Methods— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 42 publications
4
36
0
1
Order By: Relevance
“…DHA deficits may hamper neurite growth for neural development [14] and decrease soma size of hippocampus neuron and number of synaptic vesicles after learning task [15, 16]. We showed that DHA supplementation could reverse sevoflurane-induced synaptic injuries and improve the memory performance in the adulthood, which were consistent with other studies showing neuroprotective effects of DHA [17, 18]. …”
Section: Discussionsupporting
confidence: 88%
“…DHA deficits may hamper neurite growth for neural development [14] and decrease soma size of hippocampus neuron and number of synaptic vesicles after learning task [15, 16]. We showed that DHA supplementation could reverse sevoflurane-induced synaptic injuries and improve the memory performance in the adulthood, which were consistent with other studies showing neuroprotective effects of DHA [17, 18]. …”
Section: Discussionsupporting
confidence: 88%
“…How exactly n-3 PUFAs modulate microglial responses remains largely unknown, although recent studies suggest a role of DHA-containing lipid bodies and their functional interplay with mitochondria [54, 55]. We have previously found that n-3 PUFAs enhance Akt signaling after hypoxia/ischemic brain injury [56]. While Akt is known to exert anti-inflammatory effects on microglia and macrophages [14], it remains to be determined whether n-3 PUFAs induce M2 polarization after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were dehydrated and embedded in araldite and then sectioned (80 nm), counterstained with uranylacetate and lead citrate and autophagosomes were detected with a TEM. Images were acquired digitally from a randomly selected pool of 10 to 15 fields under each condition (Eskelinen, Reggiori, Baba, Kovacs, & Seglen, 2011). 2.9 | Primary cultured rat cortical neurons culture Primary rat cortical neurons were prepared from newborn SD rats as described previously (Zhang et al, 2015). In brief, the primary cortical neurons were seeded at 1 × 10 5 Áml −1 on 96-well plates or 24-well plates with poly L-lysine-coated and resuspended in DMEM/F12 which contains 10% FBS and 2% B27 supplement and then maintained in a humidified incubator (37 C, 5% CO 2 ) for 10 days.…”
Section: Transmission Electron Microscope Observationmentioning
confidence: 99%